A potential pathophysiological role for galectins and the renin-angiotensin system in preeclampsia - Blois, Sandra M. (2015)
This review discusses a potential role of galectins and the renin-angiotensin system (RAS) in the pathophysiology of preeclampsia (PE). Preeclampsia affects between 3 and 5 % of all pregnancies and is a heterogeneous disease, which may be caused by multiple factors. The only cure is the delivery of the placenta, which may result in a premature delivery and baby. Probably due to its heterogeneity, PE studies in human have hitherto only led to the identification of a limited number of factors involved in the pathogenesis of the disease. Animal models, particularly in mice and rats, have been used to gain further insight into the molecular pathology behind PE. In this review, we discuss the picture emerging from human and animal studies pointing to galectins and the RAS being associated with the PE syndrome and affecting a broad range of cellular signaling components. Moreover, we review the epidemiological evidence for PE increasing the risk of future cardiovascular disease later in life.